ترغیب و ترہیب کے اسالیب اور انسانی نفسیات :سیرتِ نبوی ﷺ کی روشنی میں تجزیاتی مطالعہ: Prophetic Methods of Encouragement and Warning and Human Psychology: An Analytical Study in the Light of the Sīrah of the Prophet Muhammad ﷺ - Muhammad AbuBakar; Dr. Muhammad Pervaiz (jihat-ul-islam, 2025)
Encouragement is such a good principle of binding human life within moral, cognitive, intellectual and ideological boundaries, examples of which are found in the Qur’an and the Sunnah of the Prophet (SWS). It is intended to be done in the light of principles. "Tagheeb" means to insist on the performance of certain matters or to hasten it, and "Tagheeb" means to inform about the harms of bad actions and its consequences. The method adopted to create interest in a good or good work is called motivation, similarly to create hatred for any matter that causes harm and danger to a person in this world or the hereafter. The style that should be adopted is called Tarheeb. The style adopted by the Holy Prophet (peace be upon him) is based on persuasion and Tarheeb. In this paper, the prophetic style based on persuasion and encouragement will be reviewed.